2007
DOI: 10.1096/fj.06-6109com
|View full text |Cite
|
Sign up to set email alerts
|

Human cord blood CD34 + cells develop into hepatocytes in the livers of NOD/SCID/γ c null mice through cell fusion

Abstract: Several studies have shown that hepatocytes can be generated from hematopoietic stem cells, but this event is believed to be rare and to require hepatic damage. To investigate this phenomenon in human cells, we used a NOD/SCID/gamma(c)null (NOG) mouse model that can achieve a tremendously high level of chimerism when transplanted with human hematopoietic cells. Even without hepatotoxic treatment other than irradiation, human albumin and alpha-1-antitrypsin-positive cells were invariably detected in the livers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2008
2008
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 32 publications
(35 reference statements)
1
27
0
1
Order By: Relevance
“…Rat MSCs can also differentiate into hepatocytes in vitro and these cells continue to function after transplantation into DPPIV-negative rats, again predominantly in the periportal area [108]. As expected, a number of transplantation studies report fusion between donor and recipient cells, including human cord blood with sublethally irradiated mouse hepatocytes [109] and mouse bone marrow with mouse hepatocytes after CCl 4 injury [110]: the benefits of cell fusion in the context of hepatocyte injury are not immediately obvious.…”
Section: Bone Marrowmentioning
confidence: 83%
“…Rat MSCs can also differentiate into hepatocytes in vitro and these cells continue to function after transplantation into DPPIV-negative rats, again predominantly in the periportal area [108]. As expected, a number of transplantation studies report fusion between donor and recipient cells, including human cord blood with sublethally irradiated mouse hepatocytes [109] and mouse bone marrow with mouse hepatocytes after CCl 4 injury [110]: the benefits of cell fusion in the context of hepatocyte injury are not immediately obvious.…”
Section: Bone Marrowmentioning
confidence: 83%
“…Dans un certain nombre de cas, ce phénomène correspond à une fusion de cellules hématopoïétiques avec les hépatocytes endogènes [31,32]. Les cellules souches mésenchymateuses (CSM) sont d'un intérêt potentiel certain, mais les données actuelles suggèrent qu'elles jouent un rôle essentiellement de support trophique dans les foies lésés en inhibant la mort des hépatocytes et en stimulant leur prolifération [33][34][35][36].…”
Section: Autres Types De Cellules Souches Sources Potentielles D'hépaunclassified
“…At the end of each time point (12,24,36,48 and 60 h), the supernatant was collected to measure the secretion of ALB and the levels of the enzymes: glutathione peroxidase (GSH-Px), super oxide dismutase (SOD) and lactate dehydrogenase (LDH). LDH activity in the supernatant was measured via spectrophotometry.…”
Section: Measurement Of Enzymes and Alb Release In The Co-culture Systemmentioning
confidence: 99%
“…Therefore, in our study, hybrid cells derived from hepatic cells have a particular function to inhibit the apoptosis of hepatic cells. It was reported that fusion occurs, under selective pressure, such as under conditions of damage [47][48][49][50]. Fusion occurred spontaneously in vivo after transplantation and in vitro after co-culturing [26,50].…”
Section: Hybrid Cells Differentiated Into Functional Hepatic Lineage mentioning
confidence: 99%
See 1 more Smart Citation